2016
DOI: 10.1124/dmd.115.067777
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro-In Vivo Extrapolation Scaling Factors for Intestinal P-glycoprotein and Breast Cancer Resistance Protein: Part II. The Impact of Cross-Laboratory Variations of Intestinal Transporter Relative Expression Factors on Predicted Drug Disposition

Abstract: Relative expression factors (REFs) are used to scale in vitro transporter kinetic data via in vitro-in vivo extrapolation linked to physiologically based pharmacokinetic (IVIVE-PBPK) models to clinical observations. Primarily two techniques to quantify transporter protein expression are available, immunoblotting and liquid chromatographytandem mass spectrometry. Literature-collated REFs ranged from 0.4 to 5.1 and 1.1 to 90 for intestinal P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP), respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 19 publications
(28 reference statements)
2
29
1
Order By: Relevance
“…), optimization and standardization, such as this work, should lead to reliable quantification and subsequently valid pharmacokinetic/pharmacodynamic conclusions (Harwood et al . ; Rostami‐Hodjegan ). Inter‐species differences between rats and humans are highlighted, in line with published literature.…”
Section: Discussionmentioning
confidence: 99%
“…), optimization and standardization, such as this work, should lead to reliable quantification and subsequently valid pharmacokinetic/pharmacodynamic conclusions (Harwood et al . ; Rostami‐Hodjegan ). Inter‐species differences between rats and humans are highlighted, in line with published literature.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the QconCAT-based dataset showed overall poor correlation with catalytic activity, with moderate correlations observed only for UGTs 1A1, 1A3, and 2B7. Therefore, these intermethodology differences suggest that effective characterization of ADME protein expression levels in different systems should ideally be complemented with specific activity data, preferably generated within the same system or tissue samples, as previously advocated (Harwood et al, 2016b). The abundance data related to UGT1A3 is an interesting case, where the expression data from the two laboratories correlated and both datasets correlated with CDCA glucuronidation activity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-laboratory study that looked into differences in measured abundances of two intestinal efflux transporters, P-glycoprotein (ABCB1) and breast cancer resistance protein (ABCG2), reported up to three-and fivefold differences in abundance measured in matched human jejunal and Caco-2 samples, respectively (Harwood et al, 2016a). However, the laboratory-specific IVIVE relative expression factors (REFs) generated for these proteins were within twofold for both transporters and did not reflect significant differences in simulated pharmacokinetic outcomes (Harwood et al, 2016b), suggesting that systematic bias in methodology can lead to valid IVIVE conclusions if more suitable study designs are implemented, where specific REF values of ADME proteins are generated in the same or a similar setting. In contrast, another cross-laboratory study that compared quantitative proteomic data of several ADME proteins (P450s, UGTs, and transporters) from six independent laboratories (Wegler et al, 2017) reported large interlaboratory differences that led, in the case of organic anion transporting polypeptide transporters, to significant discrepancies in simulated uptake clearance of atorvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…Co-culturing with HT29 cells provides a mucus layer and has been suggested to reduce the "tightness" of the tight junctions to better represent the physiology of the small intestine (Pan et al, 2015;Hilgendorf et al, 2000). Variability in expression levels of transporters can be accounted for by applying a correction factor representing the relative expression level of transporters within Caco-2 cells compared with the in vivo situation (Harwood et al, 2016). Addition of vitamin D3 to the culture medium results in increased expression of CYP3A4 (Schmieldlin-Ren et al, 1997).…”
Section: In Vitro Methods For Intestinal and Liver Metabolismmentioning
confidence: 99%
“…Though Caco-2 cells are proficient in the main transporters, including P-glycoprotein (PgP), multidrug resistance protein 2 (MRP2), and breast cancer resistance proteins (BCRP), expression levels of these transporters are generally quite variable (Larregieu and Benet, 2013;Harwood et al, 2013Harwood et al, , 2016. In addition, the under-expression of transporters such as peptide transporter 1 (PEPT1), organic cation transporters (OCTs), and organic anion transporters (OATs), makes the model less suitable for compounds that use these transporters (Larregieu and Benet, 2013).…”
Section: In Vitro Methods For Assessing Kinetics Predictive Value Fomentioning
confidence: 99%